Effect of Laser and UV Radiations on Germination, Growth and Chlorohyll Content of Brassica juncea - Pranoti R. Khawane; Dr. Sanjay K. Devade (International Journal of Scientific Research in Science and Technology, 2025)
The present study was conducted to determine the dose of red laser, green laser, UV-A, UV-B and UV-C at which the lethality of the seedling is 50%. For this purpose, the uniform seeds of Brassica juncea (mustard) variety TAM 108 were irradiated with laser and UV radiation at different time intervals. Treated and untreated seeds are kept for germination in two replicates. Accordingly, the LD 50 value of Brassica juncea is determined for the red laser, green laser, UV-A, UV-B and UV-C. The seeds treated with higher LD 50 value were analyzed together with the untreated control seeds for their degree of germination. Afterwads the time for irradiation was chosen and presowing irradiation treatment was given to the seeds and their germination, growth and chlorophyll content was studied for laser and UV radiations. The Red laser shows significant effect on germination growth as well as chlorophyll content follwed by UV A radiations. While, the UV C shows negative effect on growth, germination and chlorophyll content of Brassica juncea.
Keywords: LD 50 value; Glycine max AMS-100-39; Brassica juncea TAM-108; red laser; green laser; UV-A; UV-B; UV-C